Gorlin′s Syndrome - Chavan Rajeshree G; Phadke Vaishali A; Joshi Rajiv; Khopkar Uday; Wadhwa S L (Wolters Kluwer Medknow Publications, 1998)
Three adults (2M, 1F) with Gorlinâ€s Syndrome are presented. All three had characteristic facies, multiple small basal cell carcinomas on the centrofacial region and pitting of plams and soles. The first patient, male aged 52 year, also had ulcerated basal cell carcinomas on chest, nape of neck and left temporal region, multiple cysts, chalazion and scoliosis. Two patients had repeated episodes of periodically discharging swellings on lower jaw. Skin biopsy of the popular lesions in all three cases revealed basal cell carcinomas. All cases had radiological evidence of osseous abnormalities which included fusion of ribs and vertebrae in one case, lytic lesions of the mandiable in two cases and calcification of the flax cerebri in two cases. The small basal cell carcinomas were treated with electrodessication and cryotherapy; the larger lesions were surgically excised. Patients were counseled and continued to follow up with occasional development of new lesions.